Analisis Pengaruh Stres Kerja, Beban Kerja dan Lingkungan Kerja terhadap Turnover Intention Karyawan pada PT XL Axiata Tbk Jakarta - Laksmi Sito Dwi Irvianti; Renno Eka Verina (Binus Business Review, 2015)
This study aims to determine the effect of job stress, workload and work environment to employee turnover intention PT XL Axiata Tbk Jakarta. This study used survey research and data collection technique used are observation, interviews, literature studies and questionnaires distributed through 81 employees as respondents. The collected data was analyzed by using simple and multiple regression. From the research, it is known variables X1 (job stress) partially influence on the variable Y (turnover intention). The X2 variable (workload) partially influence variable Y (turnover intention). While the X3 variable (work environment) partially influence variable Y (turnover intention) And unknown variables X1 (job stress), X2 (workload) and X3 (work environment) influences variable Y (turnover intention) simultaneously.